Murder on tour - Burns, V. M., 1964- (Burns, V. M., 1964- Mystery bookshop mystery., 2023)
Wrapping up her book tour at a prestigious book festival in her hometown, Samantha Washington is faced with a real-life mystery with a huge plot twist when a best-selling author is accused of plagiarism and sabotage, proving to Sam that fact can be deadlier than fiction.